Characteristics and mechanism of chitosan in flocculation for water coagulation in the Yellow River diversion reservoir. (April 2020) - Chen, Faming; Liu, Wei; Pan, Zhangbin; Wang, Yonglei; Guo, Xiaoya; Sun, Shaohua; Jia, Ruibao
Highlights: Water from the Yellow River reservoir was treated with Polyaluminum chloride and a PAC/chitosan compositel. Compared with the use of PAC only, the addition of a small quantity of CTS improved the removal effect of each index indicators by 8.7 %-46.83 %. Under the same conditions, the size of the floc formed by the composite coagulant containing CTS increased by 36.67%. When long-chain bridging is dominant, It's more conducive to rapid formation of structured and dense flocs. When electrical neutralization is dominant, the flocs have better regeneration abilities. Abstract: In this paper, water from the Yellow River reservoir was treated with Polyaluminum chloride (PAC) and a PAC/chitosan (CTS) composite to study the flocculation efficiency, changes in the flocculation characteristics, and the role played by CTS in the process of coagulation. The floc microstructure was analyzed by scanning electron microscopy, and the floc characteristics and fractal dimension were studied using a laser particle size analyzer. The results showed that addition of a small quantity of CTS could produce a relatively good coagulation effect, and the removal effect of each index increased by 8.7 %–46.83 % compared with that obtained with only PAC. However, as the dose increased, the effects on various indexes did not increase significantly. Under the same conditions, the growth rate and size of flocs formed with the composite coagulant containing CTS were better than those obtained with only PAC, with an increase in the floc size about 36.67 % with CTS. The floc regeneration capacity showed the opposite trend. It is likely that when long-chain bridging is dominant, the conditions are more conducive to rapid formation of structured and dense flocs. By contrast, when electrical neutralization plays a leading role, the flocs have better disintegration and regeneration abilities.